Driving Quality and Continuous Improvement: A Tracer Study of Graduate Programs at Osias Colleges Incorporated - Castro, Rein Mark F.; Cristobal, Joseph M.; Espelita, Mark Moises A. (Future Science / FSH-PH Publications, 2025)
This tracer study examines the outcomes of the MAEd and MBA graduate programs at Osias Colleges, Inc. (OCI). Building upon a descriptive design and data from 143 alumni gathered via a validated survey, results reveal high satisfaction and engagement, particularly in teaching, research, and extension services. Although the comprehensive exam is a pivotal assessment of the students understanding and the overall outcome of their teaching and learning, a number of studies find little relationship between the exam score and the professional outcomes, such as subsequent work performance of graduate students. Recommendations include enhanced administrative support and continuous alumni engagement to strengthen program quality as well as provide a number of more relevant professional development programs and recognition programs to further strengthen program efficacy.